Maresin 1 and CHI3L1 Levels Exhibit Opposing Trends and Correlations with Renal Dysfunction in Diabetic Nephropathy - Aykut Bulu; Erhan Onalan; Burkay Yakar; Gulay Bulu; Senanur Onalan Yıldırım; Mehmet Ferit Gursu; Ugur Kaplankaya; Emir Donder; Tugce Kaymaz (Medicina, 2025)
Background and Objectives: This study aimed to investigate the relationship between Maresin-1 (MaR1), Chitinase-3-like protein 1 (CHI3L1), and inflammatory as well as hematological markers in patients with type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN). Materials and Methods: This cross-sectional study included 90 participants divided into three groups: healthy controls (n = 30), patients with T2DM (n = 30), and patients with diabetic nephropathy (n = 30). The serum levels of MaR1 and CHI3L1 were measured using ELISA. Biochemical and hematological parameters were also assessed. Statistical comparisons were conducted using non-parametric tests, and correlations were analyzed via Spearman correlation. Results: Serum MaR1 levels were significantly higher in DN patients compared to both T2DM patients and controls (p < 0.01), while CHI3L1 levels were significantly lower in the DN group compared to controls (p = 0.007). MaR1 showed a positive correlation with CRP, BUN, and creatinine, and a negative correlation with GFR. CHI3L1 levels were positively correlated with GFR and negatively with BUN. Inflammatory markers such as CRP were elevated in the diabetic groups, while no significant differences were found in NLR values. Conclusions: Elevated MaR1 levels in DN patients and their correlation with renal dysfunction markers suggest that MaR1 may serve as a potential prognostic biomarker in diabetic nephropathy. The unexpected decrease in CHI3L1 levels in DN patients indicates the need for further research to clarify their role. These findings indicated that MaR1 and CHI3L1 should be further investigated in future studies as indicators for the early detection and monitoring of diabetic complications.